1. Wykonaj mnożenie i zredukuj wyrazy podobne .
a) (a-4)(a+5)
b) (7b+3)(2-4b)
c) (-3c+2d)(2c-6)
d) (9s-2t)(7t-s)
e) (-10m+3n)(5n-4)
f) (3kl+8k)(4-2l)
g) (4xy+3x)(2y+5x²y)
h) (-2p²q-3p)(5pq-3p²q²)
2. Zapisz w jak najprostszej postaci:
a) (a+3)(a-1)+(a-7)(a+5)
b) (2b-5)(3-2b)-(3b+2)(b-6)
c) -7c²(5c-4)+(3c²+c)(6-2c)
d) 3m(m-4)(5m+2)-m(2m+3)(4-3m)
e) -2x(3x-5y)-(x+2y)(3x-y)
3. Zapisz w postaci sumy algebraicznej :
a) (x+1)(x+2)(x+3)
b) (x-2)(x+5)(2x-1)
c) (x-4)(x+1)²
d) (2x-3)²(x+2)

2

Odpowiedzi

2009-12-03T15:44:21+01:00
1. Wykonaj mnożenie i zredukuj wyrazy podobne .
a) (a-4)(a+5) = a² - 20
b) (7b+3)(2-4b) = 28b² - 6
c) (-3c+2d)(2c-6) = -6c² + 24c + 4cd - 12d
d) (9s-2t)(7t-s) = - 9s² - 14t²
e) (-10m+3n)(5n-4) = - 50mn - 40m +15n² - 12n
f) (3kl+8k)(4-2l) = 12kl - 6kl² + 32k - 16 kl = - 4kl - 6kl² + 32k
g) (4xy+3x)(2y+5x²y)
h) (-2p²q-3p)(5pq-3p²q²)
2 4 2
2009-12-03T16:05:10+01:00
A) a²+5a-4a+20
b) 14b+28b²+6+12+12b
c) -6c²+18+4dc+12d
d) 63st+9s²14t²+2ts
e) -50mn+49m+15n²+12n
f) 12kl+6kl²+32k+16kl
g) 8xy²+20x³y²+6xy+15x³y
h) -10p³q²-15p²q+6p³q³
2
a) a²+a+3a+3+a²+5a-7a-35= 2a²-2a-33
b) 6b+4b²+10b-15-3b²-18b-2b-12=-4b+1b²-27
c)-35c³+28c²+18c²+6c+6c³+18c²=-29c³+52c²+6c
d) 3m²-12m+5m²-2m-2m-8-2m²-3m+8m-6m²+12-9m=-20m+12
e) -6x+10y-3x-6y-5xy-10y²+2x²-xy+4xy-4y²==9x+4y-2xy-14y²+2xy²
3
a) 3x+6
b) 5x+8
c) 2x²+4
d) 4x³+6
1 5 1